Translation: A Multidisciplinary Approach - House, Juliane; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The cross-linguistic and cross-cultural practice of translation is a field of rapidly growing international importance. World-renowned experts offer new and multidisciplinary insights on this subject, viewing translation as social action and intercultural communication, and as a phenomenon of languages in contact and a socio-cognitive process.
Keywords: Linguistics; Literature -- Translations; Applied linguistics; Historical linguistics; Translation and interpretation; Linguistics; Applied Linguistics; Translation; Historical Linguistics; Translation Studies